ٻولي: سماجي عنصر، پاڻ مرادو اختيار ڪيل يا خالق جي عطا، هڪ تنقيدي جائزو. Language: A Social Element, Self-Acquired or a Divine Gift — A Critical Review - Latif, Abdul; Ali, Mumtaz; Memon, Atiqullah (Social Science Review Archives, 2025)
This article presents a critical review of the nature of language, its origin, evolution, and social significance. According to the article, the word “language” is derived from “speech” (bol), which means sound. Every living being produces sounds in its own way, but human language is the most refined and meaningful. Through language, humans not only communicate with one another but also establish a connection with their Creator through praise, supplication, and devotion. From an Islamic perspective, language is a special gift from Allah, which began with Prophet Adam (peace be upon him) and reached its complete form in the Arabic language during the final stage of prophethood. The article further explains that the Arabic language holds a special status because it is the language of the Holy Qur’an. Due to its association with religious practices of Muslims across the world, it has had a global influence. Many languages, including Sindhi, show a strong impact of Arabic in terms of vocabulary, grammar, and script. At the same time, the antiquity of the Sindhi language and its original sounds give it a distinct identity. Language is described as an organized system of symbols, where sounds represent different objects, emotions, and ideas. These sounds and words create mental images and serve as an effective medium of communication. Language is a fundamental element of society; without it, human society cannot exist. Social relationships, trade, culture, and civilization are all interconnected through language. The article also sheds light on the evolution of languages, stating that new languages emerged over time from early dialects. Due to interaction, trade, migration, and cultural exchange, languages underwent changes and expansion. Some languages developed further because they were preserved in written form, while others disappeared over time. In conclusion, the article states that language is a fundamental pillar of human identity, culture, and society. It is not only a means of expression but also distinguishes humans from other creatures. According to Islamic teachings, language is a divine gift, whereas linguistics considers it a result of social and evolutionary processes, and an intellectual debate continues between these two perspectives.